Theories for social justice and reduction of inequalities: a review of freirean communications. - Hayvon, John C. (Atlantic Journal of Communication)
This paper assesses the contributions of Paulo Freire to communication theories, drawing upon a search for communication theory literature on the database Communication and Mass Media Open and the conglomerate source Encyclopedia of Communication Theory. Four encyclopedia entries are reviewed alongside 22 articles. Often identified as an education theorist, Freire and his contributions to the interdisciplinary field of communication can be seen in relation to international development; sign-language interpretation; communication ethics; public communication; culture; mass media; among others. Several studies are conducted in non-Western countries, with a notable focus on multicultural communication toward peace-building and cultural harmony. Additionally, severe social justice issues which involve violation of basic human rights are documented in two indigenous studies. Eight new theory-making papers are identified, in which Freirean theory is mobilized to support communication theory-building. The intersectional and multicultural nature of Freirean theory emerges as leading to diverse applications in social justice, and the review outlines six key Freirean concepts which recur in existing communication theories and studies: dialogue; praxis; banking model; problem-posing; critical consciousness; and emancipation. How each of these concepts are mobilized to guide theorizing in the field of communication are summarized, toward supporting future work in communication as social justice practice.